Comparative Study of The Kinetics of Base Catalysed Hydrolysis of Methyl Salicylate in Aquo-Ethylene Glycol, Aquo-n-propyl Alcohol and Aquo-Tertiary Butyl Alcohol - Singh, Bhihari; Kumar Sinha, Ajay; Kumar, Akhilesh; Kumar Singh, Arvind (Asian Journal of Chemistry, 2010)
The rate of alkali catalysed hydrolysis of methyl salicylate in aquoethylene glycol, aquo-n-propyl alcohol and aquo-tertbutyl alcohol of composition ranging from 10% to 40% of ethylene glycol, n-propyl alcohol and tertiary butyl alcohol respectively at temperature varying from 15 to 35°C has been studied. The rate constant decreases with increasing percentage of ethylene glycol, n-propyl alcohol and tertiary butyl alcohol respectively in water. The isocomposition activation energy Ec was calculated using Arrhenius equation and other thermodynamic parameters such as change in enthalpy of activation ΔH*, change in free energy of activation ΔG*, and change in entropy of activation ΔS* were evaluated using Wynne Jones and Erying equation. The variation in rates and thermodynamic parameters of the reactions in the aquo co-solvent media has been compared with each other.